2013
DOI: 10.1186/1748-717x-8-65
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of poly (ADP-ribose) polymerase inhibitor ABT-888 combined with radiotherapy and temozolomide in glioblastoma

Abstract: BackgroundThe cytotoxicity of radiotherapy and chemotherapy can be enhanced by modulating DNA repair. PARP is a family of enzymes required for an efficient base-excision repair of DNA single-strand breaks and inhibition of PARP can prevent the repair of these lesions. The current study investigates the trimodal combination of ABT-888, a potent inhibitor of PARP1-2, ionizing radiation and temozolomide(TMZ)-based chemotherapy in glioblastoma (GBM) cells.MethodsFour human GBM cell lines were treated for 5 h with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 34 publications
2
53
0
1
Order By: Relevance
“…A potential therapeutic strategy would be the use of PARP inhibitors to enhance apoptosis under genotoxic damage. When the PARP inhibitor ABT-888 was used in combination with TMZ and radiation in GBM cell lines, apoptosis increased, and cells were sensitized to therapy (Barazzuol et al 2013). GBMs thrive in harsh microenvironments characterized by hypoxia and limited nutrient availability.…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…A potential therapeutic strategy would be the use of PARP inhibitors to enhance apoptosis under genotoxic damage. When the PARP inhibitor ABT-888 was used in combination with TMZ and radiation in GBM cell lines, apoptosis increased, and cells were sensitized to therapy (Barazzuol et al 2013). GBMs thrive in harsh microenvironments characterized by hypoxia and limited nutrient availability.…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…The cells were cultured as previously described in Barazzuol et al (2013). The doubling time for both cell lines was approximately 24 hours, whereas the plating efficiency was 63 ± 2% for LN18 and 24 ± 2.6% for U251.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…Patients with GBM are routinely treated with concomitant X-rays and temozolomide (TMZ), but prognosis still remains poor (Barazzuol et al 2010). Previously, we have shown that TMZ causes reproducible additive cytotoxicity when combined with radiation, regardless of the radiation types and only on 0 6 -methylguanine DNA methyltransferase (MGMT)-methylated GBM cell lines (Barazzuol et al 2011), while ABT-888 (a poly (ADP-ribose) polymerase (PARP) inhibitor) radiosensitises all tested cell lines regardless of their MGMT status (Barazzuol et al 2013). Despite advances in brain tumour treatment, it is clear that new therapies need to be developed to improve life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have led to clinical trials of PARP inhibitors in combination with chemotherapeutics that lead to DNA damage (Table 1), with the PARP inhibitor blocking the subsequent DNA repair mechanisms selectively in cancer cells. Some of the drugs being used with PARP inhibitors include platinum based DNA damaging agents such as cisplatin, carboplatin, oxaliplatin; alkylating agents like Temozolomide (TMZ) and topoisomerase inhibitors such as Camptothecin (CPT) and its derivatives (irinotecan and topotecan) [19][20][21][22][23][24][25]. TMZ therapy, when combined with radiation induces single stranded breaks (SSBs) and hence is the direct target of PARP inhibitors.…”
Section: Combination Therapy With Chemotherapeutics and Radiationmentioning
confidence: 99%